2015
DOI: 10.1002/anie.201507805
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Isoquinoline and Substituted Quinolines in Charged Microdroplets

Abstract: A Pomeranz-Fritsch synthesis of isoquinoline and Friedländer and Combes syntheses of substituted quinolines were conducted in charged microdroplets produced by an electrospray process at ambient temperature and atmospheric pressure. In the bulk phase, all of these reactions are known to take a long time ranging from several minutes to a few days and to require very high acid concentrations. In sharp contrast, the present report provides clear evidence that all of these reactions occur on the millisecond timesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
166
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 43 publications
2
166
1
7
Order By: Relevance
“…Fort he above three reactions (Figures 2, 3, and 4), we performed control studies with normal filter paper without the embedded nanocatalysts.N one of the control studies (data not shown) was able to catalyze any of the above reactions in the absence of catalytic nanoparticles.W ea lso performed av oltage-dependent study of those reaction (Figures 2, 3, and 4). On changing the paper spray voltages from 0t oÀ7kV, the reaction efficiencies (formation of intermediates and products) increased (Supporting Information, Figures S15 and S16), which indicates the requirement of abasic environment for these reactions,which is provided by the abundant solvent (water) reduction at elevated negative voltages.Itshould be noted that the increased negative spray voltage can also improve the ionization efficiencya nd ion detection sensitivity in mass spectrometry,w hich can also contribute to modifying the product-to-reactant ratios [20] (Supporting Information, Figures S15 and S16). We also investigated the addition of base to the reaction mixture (pH % 11) but found no increase in the reaction yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Fort he above three reactions (Figures 2, 3, and 4), we performed control studies with normal filter paper without the embedded nanocatalysts.N one of the control studies (data not shown) was able to catalyze any of the above reactions in the absence of catalytic nanoparticles.W ea lso performed av oltage-dependent study of those reaction (Figures 2, 3, and 4). On changing the paper spray voltages from 0t oÀ7kV, the reaction efficiencies (formation of intermediates and products) increased (Supporting Information, Figures S15 and S16), which indicates the requirement of abasic environment for these reactions,which is provided by the abundant solvent (water) reduction at elevated negative voltages.Itshould be noted that the increased negative spray voltage can also improve the ionization efficiencya nd ion detection sensitivity in mass spectrometry,w hich can also contribute to modifying the product-to-reactant ratios [20] (Supporting Information, Figures S15 and S16). We also investigated the addition of base to the reaction mixture (pH % 11) but found no increase in the reaction yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1] Confined volumes can take the form of sprays,g enerated by nebulization using electric and/ or magnetic fields,o rt hin films,g enerated for example by drop casting.F or instance,the Hantzsch reaction proceeds in 90 %y ield in charged microdroplets generated by electrospray. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes.…”
mentioning
confidence: 99%
“…[2] Base-catalyzed Claisen-Schmidt condensation is accelerated in electrosprayed droplets, [3] in levitated Leidenfrost droplets, [4] and in the paper spray experiment that combines athin film format with charged droplet emission. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes. [10] The underlying reasons for acceleration are increased reagent reactivity,d ue to partial desolvation at the interface, [11] pH value change, [12] and increased reagent concentration associated with solvent evaporation.…”
mentioning
confidence: 99%
“…It has become apparent that the environment in microdroplets is strikingly different from that of the corresponding bulk phase . Many features of microdroplets may contribute to reaction acceleration, such as the confinement of reagents in small‐volume reactors, the large surface‐to‐volume ratios of small reactors, the higher density of molecules on the surface of the microdroplets, solvent evaporation with associated increases in reagent concentrations, and extreme pH values . Thus far, most of the reported accelerated reactions in microdroplets mirror the products found in the bulk reaction .…”
Section: Figurementioning
confidence: 99%